A102 INDICATION FOR ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY AND ASSOCIATION WITH HEMORRHAGE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (21st February 2022) - Parvizian, M K; Zhang, M; Edwards, M; Bhoey, P; Hookey, L; Rodrigues, D
Abstract: Background: Hemorrhage is a complication associated with up to 2% of cases of Endoscopic Retrograde Cholangiopancreatography (ERCP), most commonly following sphincterotomy. Studies investigating risk factors associated with hemorrhage, such as ERCP indication, have been conflicting. Aims: We performed a systematic review and meta-analysis to determine the association between the indication for ERCP and ERCP-associated hemorrhage. Methods: A systematic search of MEDLINE, EMBASE, and CENTRAL was done from inception until September 2021 for studies reporting on factors associated with ERCP-associated hemorrhage (both immediate and delayed) in adults. Exclusion criteria included: pediatric patients, no outcome of interest, did not investigate hemorrhage risk factors, inappropriate study design (basic science, reviews, and case reports/series), or if no English text was available. A DerSimonian and Laird random-effects meta-analysis was performed to generate pooled Odds Ratios (OR) with 95% Confidence Intervals (CIs) for each procedural indication in relation to hemorrhage. Results: 952 records were identified of which 17 were included in our quantitative analysis. Common indications included acute cholangitis, choledocholithiasis, Sphincter of Oddi dysfunction (SOD), acute pancreatitis, chronic pancreatitis, and malignancy-associated duct obstruction. Rates of hemorrhage varied in the included studies (median 2.2%; IQR 1.7–6.9). Sphincterotomy rates also differed in the included studies (median 100%; IQR 71.1–100). Five studies did not report on antiplatelet or anticoagulant use with the remaining reporting varying rates of antiplatelet (median 8.3%; IQR 0–26.5) and anticoagulant (median 0.8%; IQR 0–2.25) use. Hemorrhage was significantly associated with acute cholangitis (OR 2.48; 95% CI 1.62–3.78) and choledocholithiasis (OR 1.76; 95% CI 1.06–2.94) but not SOD (OR 1.38; 95% CI 0.74–2.58), malignancy (OR 0.68; 95% CI 0.29–1.59), acute pancreatitis (OR 1.08; 95% CI 0.30–3.82), or chronic pancreatitis (OR 0.56; 95% CI 0.16–1.99). Conclusions: Acute cholangitis and choledocholithiasis were associated with increased hemorrhage, whereas SOD, malignancy, acute pancreatitis, and chronic pancreatitis were not. Providers should consider procedural indication when counselling patients on hemorrhage risk in ERCP. Funding Agencies: None